Evaluating the nexus of funding and scientific output in Kazakhstan - Abdikadirova, Anar; Sembiyeva, Lyazzat; Temirkhanov, Zharaskhan; Popov, Anatoli I.; Suchikova, Yana (Business Perspectives, 2024)
This study examines the dynamics and effectiveness of investments in Kazakhstan’s research and development (R&D). The primary aim is to assess the efficiency of scientific research activities in Kazakhstan by analyzing the relationship between R&D investments and scientific outputs across different periods. As a methodological approach, Data Envelopment Analysis (DEA) calculates efficiency indicators by transforming multiple inputs into outputs. Descriptive analysis comprehensively explains trends and patterns in R&D funding, scientific publications, and patent registrations. The results reveal a substantial increase in R&D expenditure. Despite this, the share of domestic R&D expenditures from the gross domestic product (GDP) declined from 0.25% to 0.12%. The analysis also uncovered a significant surge in scientific publications, with Scopus publications increasing from 1,799 to 28,280 and Web of Science publications rising from 1,468 to 20,532 across the study period. However, a contrasting trend was observed in patent registrations, which decreased from 6,968 to 2,612, indicating potential inefficiencies in translating research into innovations. The study concludes that while Kazakhstan has demonstrated notable progress in enhancing research output, the decline in patent registrations relative to the increase in R&D investments underscores the need for strategic initiatives. These should strengthen industry-academia collaboration, enhance innovation infrastructure, and balance incentives for publications and patents, ensuring that R&D investments translate into tangible innovations and contribute effectively to the nation’s socio-economic development. © 2024 LLC CPC Business Perspectives. All rights reserved. --//-- This is an open access article Anar Abdikadirova, Lyazzat Sembiyeva, Zharaskhan Temirkhanov, Anatoli I. Popov and Yana Suchikova (2024). Evaluating the nexus of funding and scientific output in Kazakhstan. Knowledge and Performance Management, 8(1), 17-31. doi:10.21511/kpm.08(1).2024.02 published under the CC BY 4.0 licence.
Grants, a prevalent funding tool, support specific research projects financially. They have been shown to boost scientific progress, with grant recipients often achieving higher productivity and societal impact through influential publications and research results (Khamis et al., 2018; Hussinger & Carvalho, 2021). Grants also encourage collaboration and knowledge exchange, requiring interdisciplinary or international partnerships. However, the competitive nature and complex application processes can limit access for some researchers (Bennett & Gadlin, 2012; Paterlini, 2023).
Keywords: funding models; indicators; R&D investment; research evaluation; research policy; scientific publications; Scopus; Research Subject Categories::SOCIAL SCIENCES